(untitled) (Mustansiria Dental Journal, 2018)
The present study was carried out to investigate the effect of 5 cleaning agents (dettol soap, whitening tooth paste, sodium bicarbonate powder, and ethanol hand sanitizer gel and siwak powder) on color alteration of heat-polymerized acrylic resin and to compare it with that of distilled water. 60 specimen strips of heat-polymerized acrylic resin material were prepared measuring 5mm width, 40mm length and 2mm thickness; five specimens were used for each group. After two weeks of immersion in tea solution, the light transmission percent value for each specimen was determined at 400nm and 700nm wave lengths by a spectrophotometer device. Then the half of the stained specimens were cleaned by the cleaning agents by brushing with a hand brush , and rest specimens were cleaned by the same cleaning agents by an electrical dental brush and again measure the light transmission percent value for each specimen by the spectrophotometer device. The result obtained in this study showed that ethanol gel specimen group has the highest mean value for light transmission among all the specimen groups of hand and motor brush at the two wave lengths, followed by tooth paste, siwak powder, sodium bicarbonate powder & dettol soap groups but distal water group has the lowest one. Furthermore, there were no measurable differences between the hand brush and the electric tooth brush with respect to staining removal from the acrylic resin specimens for all cleaning agents groups used in this study.